Country Of Origin Effect On Organizational Innovation In Malaysia: The Mediating Role Of Structure - Mohd. Nasurdin, Aizzat; Muhamad Jantan , Muhamad Jantan; Ahmed Fadzil, Nur Fitriah (Asian Academy of Management (AAM), 2004)
The two main objectives of this study are: first, to determine whether the level of innovation (technological and process, product and administrative) varies by country of origin, and second, to investigate the influence of country of origin on organizational innovation (technological and process, product and administrative) via the mediating role played by organizational structure (formalization and centralization), among firms operating in Malaysia. Statistical analyses of the 80 multinational corporations and 43 locally-owned firms and joint-ventures using ANOVA revealed that significant differences do exist in terms of their innovation levels. Firms from the West (American multinationals and European multinationals) had higher levels of technological and process innovation compared to firms from the East (Eastern multinationals plus local companies and jointventures). Regarding product innovation, American multinationals were found to be more innovative compared to European multinationals and firms from the East (Eastern multinationals plus local firms and joint-ventures). In terms of administrative innovation, American multinationals were found to be most innovative followed by European multinationals, and lastly, firms from the East (Eastern multinationals plus local companies and joint-ventures). Additionally, country of origin had no indirect effect on the three forms of innovation via structure. Implications and suggestions for future research are discussed.